Форми та компоненти реалізації ефективної підготовки майбутнього викладача до застосування медіатехнологій у професійній діяльності - Дем'янчук, Олександр; Demjanchuk, Aleksandr; Саварин, Павло; Savaryn, Pavlo (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті коротко охарактеризовано поняття «медіатехнології» та необхідність їх застосування у педагогічній діяльності. Проведено аналіз процесу підготовки майбутнього викладача до застосування медіатехнологій в умовах інформаційного суспільства. Розглянуто та описано основні форми та шляхи підготовки майбутнього викладача до застосування медіатехнологій. Детально розглянуто різноманітні види та складові дефініції «готовність». Розроблено та обґрунтовано компоненти реалізації ефективної підготовки майбутнього викладача до застосування медіатехнологій у професійній діяльності. The paper put forward the issue of knowledge transfer and receipt of information technology. In particular, the analysis of research scientists of the problem, and briefly described the concept of «media technologies» and the need for their use in educational activities. The analysis of the process of preparation of the future teacher to use media technologies in the information society. Consider and describe basic forms and ways of training future teacher to use media technologies. Generally, there are two ways of driving targeted training of future teachers of technical subjects to the use of media technologies in their professional activities. The first – the concept of media technologies included in the Master training course, the second – the selection of self-training course masters to use media technologies in their professional activities. In detail the different types and components of the definition of «readiness». To expand the meaning of «readiness of the future teachers of technical subjects to the use of media technologies in professional activity», based on the processed literature singled out four components: psychological readiness, theoretical readiness, practical readiness, creative readiness. Developed and proved effective implementation of the components of the preparation of the future teachers of technical subjects to the use of media technologies in professional activities such as: organizational component, motivational component, cognitive component, operational component, creative and effective components. In order to provide feedback to manage the preparation of future teachers of technical subjects to the use of media technologies in teaching activities through analysis of the results of creative activity, self-monitoring and corrective work.
Forms and Components of Effective Implementation of theTraining of the Future Teacher to Use Media Technologies in Professional Activity
Keywords: готовність; ефективна підготовка; професійна діяльність; медіатехнології; readiness; effective training; professional activity; media technology